المخاطر المترتبة على الاعتماد المستندي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The purpose of this study is to highlight on the risks that the parties of the documentary credit ( the applicant, the beneficiary and the bank ) may face, because of the risk surrounding this banking operation which may lose the credit's importance in the field of the international trade. So, we had studied these risks by clarifying the difficulties that facing the applicant and the beneficiary of the credit. After that, we studied the hardest and the most important risk: the difficulties which facing the bank to implement its obligations. Finally, the researcher reached to a set of  results, and gave some recommendations to prevent such problem. يهدف هذا البحث إلى الوقوف على المخاطر التي يمكن أن يتعرض لها أطراف الاعتماد المستندي (الآمر, المستفيد, البنك), نظراً للخطورة التي تكتنف هذه العملية المصرفية والتي قد تفقده أهميته التي يتمتع بها في مجال التجارة الدولية. ولتحقيق هذا الهدف تمت دراسة هذه المخاطر من خلال توضيح الصعوبات التي يتعرض لها الآمر بفتح الاعتماد, وكذلك المستفيد من هذا الاعتماد. ومن ثم الانتقال إلى دراسة الصعوبات التي تعترض البنك في سبيل تنفيذه لالتزاماته, وهي الأصعب والأهم. واخيراً خلص البحث لعدة نتائج, دفعت الباحث لتقديم عدد من التوصيات للحيلولة دون الوقوع في هذه المشكلات.